Akibat Hukum Pembatalan Sepihak Oleh Konsumen Dalam Transaksi Jual Beli Melalui Marketplace Shopee Dengan Sistem Pembayaran Cash On Delivery Shopee - I Nyoman Putu Budiartha; Ida Ayu Putu Tania Krisna Dewi; I.B. Gede Agustya Mahaputra (Jurnal Analogi Hukum, 2025)
In the modern era, cash on delivery transactions are in great demand by the public because they provide convenience. However, behind the convenience offered, consumers often make unilateral cancellations by refusing to pay for orders, this is a default that can have legal consequences. The main problem found in this research is how is the regulation of the cancellation of sales and purchase transactions carried out unilaterally by consumers with the cash on delivery system in the Shopee marketplace? And what are the legal consequences of unilateral cancellation by consumers in cash on delivery transactions at the Shopee marketplace?. By using a normative type of legal research with a legislative approach. The conclusion of this research is that Shopee allows consumers to cancel cash on delivery orders unilaterally with several conditions. While the legal consequences received by consumers are that the consumer can be sued based on Article 6 and Article 5 of Law No. 8 of 1999 and Article 1513 of the Civil Code. The seller can also sue consumers to claim compensation as stipulated in Article 1243 of the Civil Code and Article 21 paragraph (4) of Law No. 19 of 2016.